2020
DOI: 10.1155/2020/8565760
|View full text |Cite
|
Sign up to set email alerts
|

Catharanthus roseus Combined with Ursolic Acid Attenuates Streptozotocin-Induced Diabetes through Insulin Secretion and Glycogen Storage

Abstract: Catharanthus roseus (C. roseus) and ursolic acid (UA) are ayurvedic medicines with multiple pharmacological activities including antidiabetic activity, but till date, no study is available on their combination. This study documented the antidiabetic efficacy of the combination of C. roseus and UA in rats. Rats were divided into six groups. All groups were given a single dose of Streptozotocin (STZ) at a dose of 50 mg/kg by intraperitoneal route for induction of diabetes, except the normal control group. Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…In Wistar rats exposed to STZ (50 mg/kg, single injection), 28 days of ursolic acid treatment (50 mg/kg/day, oral gavage) reduced blood glucose with similar efficacy as glimepiride. Although ursolic acid treatment significantly elevated plasma insulin levels compared to diabetic control animals, circulating levels were not completely restored to non-diabetic control values as observed with glimepiride [186]. Similarly, in diabetic Wistar rats (STZ 30 mg/kg, 2 injections), 14 days of ursolic acid treatment (200 mg/kg/ day, i.p.…”
Section: In Vivo Studiesmentioning
confidence: 87%
See 1 more Smart Citation
“…In Wistar rats exposed to STZ (50 mg/kg, single injection), 28 days of ursolic acid treatment (50 mg/kg/day, oral gavage) reduced blood glucose with similar efficacy as glimepiride. Although ursolic acid treatment significantly elevated plasma insulin levels compared to diabetic control animals, circulating levels were not completely restored to non-diabetic control values as observed with glimepiride [186]. Similarly, in diabetic Wistar rats (STZ 30 mg/kg, 2 injections), 14 days of ursolic acid treatment (200 mg/kg/ day, i.p.…”
Section: In Vivo Studiesmentioning
confidence: 87%
“…To our knowledge, ursolic acid has not been studied in genetic rodent models of T1DM and T2DM. However, in models of induced hyperglycemia (STZ) and glucose intolerance (HFD), ursolic acid has been shown to exert positive effects on circulating levels of insulin and glucose [185][186][187][188]. Furthermore, studies in patients with metabolic syndrome have also shown anti-diabetic effects [189].…”
Section: Ursolic Acidmentioning
confidence: 99%
“…In addition to its anti-inflammatory effects, recent studies showed that UA improves insulin resistance and hyperinsulinemia in diet-induced obesity rats [249][250][251]. Indeed, UA administration decreased body weights and blood glucose via angiotensin II type 1 receptor (AT1R)-associated protein 1 (ARAP1)/AT1R pathway in db/db mice [252].…”
Section: Ursolic Acidmentioning
confidence: 99%
“…When compared to dichloromethane and methanol extracts, which dropped blood glucose levels by 49-58 percent in diabetic rats, the aqueous extract was found to lower blood glucose by roughly 20%. The enhanced glucose consumption in the liver has resulted in the hypoglycemic impact.In a mouse insulinoma cell line, vindoline was discovered to raise insulin levels (MIN6) (Alkreathy HM and Ahmad A, 2020) [2] . Pharmacological studies of alkaloids obtained from C. roseus have been conducted, and a medicine developed from the plant has been sold as a diabetes cure under the brand name Vinculin (Jai Narayan Mishra et al, 2017) [18] .…”
Section: Antidiabetic Potential Of Sadabaharmentioning
confidence: 99%